Cytoprotective Actions of Omeprazole in Indomethacin – Induced Gastric Mucosal Injury in Rats. - Manna, Mohammed J.; Matloub, Samir Y. N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Gastric mucosal injury induced by NSAIDs is a major adverse effect of this group of medications, and it is no surprise that protection against such injury has become an important challenge for a better understanding of the mechanisms involved.Materials and methods: This study was conducted on 40 adult male albino rats , divided into 4 groups, the first served as a control received the vehicle , the second received indomethacin orally of 60mg/kg .The third was pretreated 30 minutes prior indomethacin with omeprazole 40mg/kg orally. The fourth was given intraperitoneal L-NAME 20mg/kg plus omeprazole to investigate a possible protective role of nitric oxide. The rats were then sacrificed after 4 hours and their stomachs were isolated and submitted to macroscopical, and microscopical assessment and for the measurement of the gastric prostaglandin E2, myeloperoxidase , and interlukin-4 .Results: Omeprazole pretreatment resulted in a significant decrease (p